Performance Analysis of SPV Module Using Solar PVTR System - Suresh Babu, G; Prem Charan, B; Murali Krishna, T (International Journal of Engineering and Technology, 2018)
With a spurt in the use of non-conventional energy sources, photovoltaic installations are being deployed in several applications such as distributed power generation and standalone systems. Solar Photo Voltaic (SPV) module is the basic component of the solar PV system. The functioning of a photovoltaic array is influenced by solar insolation, shading and array arrangement. Often the PV arrays get shadowed, completely or partially by neighboring buildings, trees, towers and service poles. The efficacy of PV array unvaryingly depends upon temperature which in turn is reliant on radiation. In order to validate this hypothesis, there are certain instruments and experimentation methods available which are expensive. But carrying out hardware testing on the solar PV system with Photo Voltaic Training and Research (PVTR) system and simulating using software will lead to least economical method of achieving performance analysis which is the main objective of this paper.Â  The efficiency of PV module is analyzed from I-V and P-V characteristics for this standalone solar pv system by changing radiation and temperature parameters. This paper mainly emphases on comparison of the testing results and simulation results for different radiation levels.Â Â